Efektivitas Pelatihan Bekam Sunnah terhadap Tingkat Pengetahuan Mahasiswa Keperawatan di Thailand: The Effectiveness of Sunnah Cupping Therapy Training on Knowledge Among Nursing Students in Thailand - Yuniarsih, Sri Mumpuni; Hasanah, Nunung; Martani, Rahajeng Win; Nahdliyyah, Ade Irma (Chakra Brahmanda Lentera Institute, 2026)
This international community service programme introduced Sunnah cupping therapy (Hijama) to nursing students at Boromarajonani College of Nursing, Nopparat Vajira, Thailand. The programme aimed to enhance participants’ understanding of traditional Islamic medicine and to foster cultural competence within nursing education. This community service programme used a pre-experimental design to evaluate participants’ knowledge of Sunnah cupping therapy. A total of 54 participants, including 46 nursing students and eight faculty members, took part in the study. The variable measured was knowledge about Sunnah cupping, assessed using a pre- and post-test questionnaire designed to measure changes in participants’ understanding. The pre- and post-test scores showed a significant increase from 56.7 to 82.5 (p < 0.001), indicating the effectiveness of the educational intervention. Participants reported greater appreciation of the holistic and spiritual dimensions of Sunnah cupping and its relevance to patient-centred care. Despite limitations such as the short duration and differing traditional medicine regulations between Indonesia and Thailand, the programme successfully met its objectives. This initiative highlights the importance of integrating cultural and traditional health perspectives into nursing curricula to promote culturally responsive care and strengthen international academic collaboration.